Tanaidacea (Tanaidacea: Crustacea) from Brazil. IV. A new genus and two new species from the family Leptocheliidae - de L. Araújo-Silva, Catarina; Larsen, Kim (Zootaxa, 2012)
This study is based on the material collected from REVIZEE Program and under the Petrobrás oil-exploration programs.These collections revealed a number of representatives from the family Leptocheliidae in its broadest sense, with descrip-tions of one new genus, Makraleptochelia n. gen., and two new species, M. potiguara n. sp. and Intermedichelia jesserin. sp. The new genus appears to be closely related to Konarus-Parakonarus-Pseudoleptochelia complex of species anddiffers mainly in the extremely elongated habitus of the male. Intermedichelia jesseri is only the second recorded speciesof this genus and is separated from the other species by having two distal simple setae on the lateral projections of pere-onite 3, two distal simple setae on the maxilliped basis, one ventrodistal spiniform seta on the merus-carpus-propodus ofpereopod 3, and pereopods 4 and 5 propodus with one dorsodistal simple seta marginally longer than dactylus and unguis combined. Intermedichelia is here included in the family Leptocheliidae.